Dispersal barriers and opportunities drive multiple levels of phylogeographic concordance in the Southern Alps of New Zealand - Marske, Katharine A.; Thomaz, Andréa T.; Knowles, L. Lacey (Molecular ecology, 2020)
Phylogeographic concordance, or the sharing of phylogeographic patterns among codistributed species, suggests similar responses to topography or climatic history. While the orientation and timing of breaks between lineages are routinely compared, spatial dynamics within regions occupied by individual lineages provide a second opportunity for comparing responses to past events. In environments with complex topography and glacial history, such as New Zealand's South Island, geographically nested comparisons can identify the processes leading to phylogeographic concordance between and within regional genomic clusters. Here, we used single nucleotide polymorphisms (obtained via ddRADseq) for two codistributed forest beetle species, Agyrtodes labralis (Leiodidae) and Brachynopus scutellaris (Staphylinidae), to evaluate the role of climate change and topography in shaping phylogeographic concordance at two, nested spatial scales: do species diverge over the same geographic barriers, with similar divergence times? And within regions delimited by these breaks, do species share similar spatial dynamics of directional expansion or isolation‐by‐distance? We found greater congruence of phylogeographic breaks between regions divided by the strongest dispersal barriers (i.e., the Southern Alps). However, these shared breaks were not indicative of shared spatial dynamics within the regions they delimit, and the most similar spatial dynamics between species occurred within regions with the strongest gradients in historical climatic stability. Our results indicate that lack of concordance as traditionally detected by lineage turnover does not rule out the possibility of shared histories, and variation in the presence and type of concordance may provide insights into the different processes shaping phylogeographic patterns across geologically dynamic regions.